COMMENTS ON THE TOBACCO INDUSTRY LABOR MANAGEMENT COMMITTEE. (Tufts Archival Research Center, 2007)
Marginalia; Speech given by Susan Stuntz regarding the tobacco Industry's relationship with labor and how the LMC is facilitating it. Gives brief history of the LMC. Lists affiliated unions. Explains ways the LMC has framed tobacco issues to make them attractive to labor unions and describes how beneficial this relationship is.